1990
DOI: 10.1007/bf00193010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of virus infection on symplastic transport of fluorescent tracers in Nicotiana clevelandii leaf epidermis

Abstract: The molecular weight exclusion limit of plasmodesmata in subveinal epidermal cells of Nicotiana clevelandii (Gray) leaves was estimated by microinjection and fluorescence microscopy using fluorescein isothiocyanate-peptide conjugates, carboxyfluorescein and Lucifer Yellow CH. The largest fluorochrome which moved symplastically between cells had a molecular weight of 749, although movement did not appear to depend purely on molecular weight parameters. Systemic infection of plants by tobacco rattle tobravirus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Surprisingly, we found that SA treatment alone could, to a limited extent, actually increase the SEL of PD linking tobacco epidermal cells (Table II). The basal SEL of tobacco epidermal cell PD has been reported to be 1 kD or less (Derrick et al, 1990), but we found, in line with the data of Poirson et al (1993), that PD of tobacco epidermal cells frequently permitted the passage of a 3-kD dextran (Table II; movement occurred in 52% of impalements). Furthermore, SA treatment caused the cell-to-cell movement of 3-kD dextran in almost all injections (Table II; movement occurred in 93% of impalements).…”
Section: Sa Does Not Inhibit Pd Gatingsupporting
confidence: 89%
“…Surprisingly, we found that SA treatment alone could, to a limited extent, actually increase the SEL of PD linking tobacco epidermal cells (Table II). The basal SEL of tobacco epidermal cell PD has been reported to be 1 kD or less (Derrick et al, 1990), but we found, in line with the data of Poirson et al (1993), that PD of tobacco epidermal cells frequently permitted the passage of a 3-kD dextran (Table II; movement occurred in 52% of impalements). Furthermore, SA treatment caused the cell-to-cell movement of 3-kD dextran in almost all injections (Table II; movement occurred in 93% of impalements).…”
Section: Sa Does Not Inhibit Pd Gatingsupporting
confidence: 89%
“…Plasmodesmata are dynamic, gatable channels that traverse the cell wall, providing a means for intercellular communication. Fluorescent tracers up to only Mr 1000 move symplastically in dye-coupling experiments (Erwee & Goodwin, 1985;Derrick et al, 1990). Wolf et al (1989) reported the same result concerning the gating capacity of tobacco plasmodesmata, suggesting an effective pore diameter of 0.73 nm.…”
supporting
confidence: 60%
“…As the M r of the cascade blue allows it to diffuse freely through plasmodesmata (Derrick et al, 1990), no movement of this dye was recorded after vacuolar injection (about 30 % of the total number of injections) and the result was then discounted. At least six to nine cytoplasmic injections were made for each plant.…”
Section: Short Communicationmentioning
confidence: 99%
“…In Nicotiniana clevelandii (Gray) we have shown previously that the molecular exclusion limit of plasmodesmata is approximately 750 Da (Derrick et al, 1990). It is possible that the desmotubule itself functions as the hypothetical 'valve' postulated by Barclay and Fensom (1 984).…”
Section: Pressure Clamp Experimentsmentioning
confidence: 96%